2018
DOI: 10.3390/toxins10120512
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Enhances MC-LR-Induced Changes on Splenic Oxidation Resistance and Innate Immunity in Male Zebrafish

Abstract: Hazardous contaminants, such as nitrite and microcystin-leucine arginine (MC-LR), are released into water bodies during cyanobacterial blooms and may adversely influence the normal physiological function of hydrobiontes. The combined effects of nitrite and MC-LR on the antioxidant defense and innate immunity were evaluated through an orthogonal experimental design (nitrite: 0, 29, 290 μM; MC-LR: 0, 3, 30 nM). Remarkable increases in malondialdehyde (MDA) levels have suggested that nitrite and/or MC-LR exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 81 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…These activities may result in eutrophication and development of cyanobacterial blooms [1,2]. The monocyclic heptapeptide microcystins (MCs) are the secondary products of cyanobacteria metabolism and most harmful cyanotoxin found in water bodies [3,4,5]. More than 200 isomers of MCs have been identified from cyanobacterial blooms, with MC-LR being the most widely distributed, abundant and toxic [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These activities may result in eutrophication and development of cyanobacterial blooms [1,2]. The monocyclic heptapeptide microcystins (MCs) are the secondary products of cyanobacteria metabolism and most harmful cyanotoxin found in water bodies [3,4,5]. More than 200 isomers of MCs have been identified from cyanobacterial blooms, with MC-LR being the most widely distributed, abundant and toxic [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that fish largely rely on the nonspecific immune system, which is tightly linked to the oxidant-antioxidant balance of the immune organs. Our previous study demonstrated that 30 µg/L of pure MC-LR resulted in a significant decrease in splenic GSH content in zebrafish [111]. GSH could exert a detoxification effect by binding MCs to form MC-GSH conjugates, and the reduction in cytosol GSH implied an excessive ROS production [112,113].…”
Section: Oxidative Stressmentioning
confidence: 99%